Knowledge on agroecology disseminated by the FAO: Assessment from a human-nature relationship perspective - Murriel Gonzales, Federico Augusto; Dessein, Joost; Adriaensens, Jonas (The International Journal of Sociology of Agriculture and Food, 2025)
This study assesses the knowledge on agroecology disseminated by the Food and Agriculture Organisation (FAO) through its Agroecology Knowledge Hub (AKH), from a human-nature relationship perspective. It focuses on the knowledge contained in scientific articles published between 2014 and 2023. Using a theoretical framework based on the concept of human-nature relationship and a methodology rooted in content analysis techniques, the study seeks to answer the following research question: What knowledge on agroecology that contributes to the reconnection between humans and nature has the FAO disseminated during the period 2014-2023? To this end, the study: (1) depicts the main trends and geopolitical distribution of the knowledge disseminated through the AKH during the specified period, (2) reveals the human-nature relationship perspectives embodied in this knowledge, and (3) delves into the state of this knowledge. The findings suggest that the knowledge disseminated through the FAO’s AKH does not fully contribute to the reconnection between humans and nature within the agricultural realm. The discrepancy may be attributed to patterns of coloniality of knowledge, the preference for disseminating knowledge rooted in positivist/post-positivist foundations and in an extractivist logic and a mechanistic view of nature, and the potential perpetuation of the Western worldview in the production of knowledge. The study concludes by urging the FAO to take ethical responsibility for its knowledge dissemination, and recommends that knowledge producers challenge prevailing theoretical frameworks and epistemological positions guiding the generation of knowledge on agroecology.